Pengaruh Penggunaan E-LKPD Berbasis Liveworksheets dalam Meningkatkan Hasil Belajar Siswa di SMP Negeri 14 Kota Serang IPA Kelas 7 Materi Bumi dan Tata Surya - Anas Ansoriyah; Supardi Supardi (Pentagon : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2025)
This study aims to determine the effectiveness of the use of Electronic Student Worksheets (E-LKPD) based on Liveworksheets in improving the learning outcomes of class VII students of SMP Negeri 14 Kota Serang on the Earth and Solar System material. LKPD functions to connect teaching and learning activities so that effective interactions occur between students and teachers, which can increase student activity to improve academic achievement. This study aims to identify improvements in student learning outcomes using ELKPD liveworksheet. This study uses a quantitative research type with a Pre-experimental design that collects and analyzes numerical data using research instruments. One Group Pretest - Posttest Design is a written design used which is combined with library research, namely using various supporting literature references in the data collection process without going into the field. Thus, it can be concluded that E-LKPD Liveworksheet is effective as a learning medium to improve student learning outcomes on the Earth and Solar System material